PHYSICOCHEMICAL MODEL FOR THE GENERATION OF THE ISOTOPIC COMPOSITION OF THE CARBONATE TRAVERTINE PRODUCED BY THE TOKHANA SPRING, MOUNT ELBRUS AREA, NORTHERN CAUCASUS - Bychkov A.Yu.; Kikvadze O.E.; Lavrushin V.Yu.; Kuleshov V.N. (My University, 2007)
The isotopic composition of calcite from travertine deposits of the Tokhana-Verkhnii hot spring in the Elbrus area shows broad variations in δ13C and δ18O (from +3.8 to +16.3‰ and from +24.6 to +28.1‰, respectively). The δ13C and δ18O values increase toward the sole of the travertine dome. The isotopically heaviest carbonates (δ13C of up to +16.3‰) were found near the bottom of the dome and composed ancient travertine, which are now not washed by mineral water. The scatter of the δ13C values of the fresh sample is slightly narrower: from +3.8 to +10‰. Calculations indicate that all carbonates of the Tokhana dome were not in equilibrium with spontaneous carbon dioxide released by the spring ( d13 CCO2 \delta ^{13} C_{CO_2 } = −8‰). To explain the generation of isotopically heavy travertine, a physicochemical model was developed for precipitation of Ca carbonates during the gradual degassing of the mineral water. The character of variations in the calculated δ13C values (from +5.5 to +13‰) is in good agreement with the tendency in the variations of the δ13C in the carbonate samples. The calculated and measured pH values are also consistent. Our results demonstrate that the isotopic composition of large travertine masses can be heterogeneous, and this should be taken into account during paleoclimatic and paleohydrogeological reconstruction.